2018
DOI: 10.3389/fphar.2018.00587
|View full text |Cite
|
Sign up to set email alerts
|

α2- and β2-Adrenoreceptor-Mediated Efficacy of the Atypical Antidepressant Agomelatine Combined With Gabapentin to Suppress Allodynia in Neuropathic Rats With Ligated Infraorbital or Sciatic Nerve

Abstract: Previous data showed that neuropathic pain induced by mechanical lesion of peripheral nerves has specific characteristics and responds differently to alleviating drugs at cephalic versus extracephalic level. This is especially true for tricyclic antidepressants currently used for alleviating neuropathic pain in humans which are less effective against cephalic neuropathic pain. Whether this also applies to the antidepressant agomelatine, with its unique pharmacological properties as MT1/MT2 melatonin receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…The study of Aydın et al revealed the curative effect of agomelatine on painful diabetic neuropathy in rats and suggested that these effects are mediated by rising synaptic catecholamine levels and through interactions with both α- and β-adrenoceptors [ 22 ]. The study of M’Dahoma et al revealed that co-administration of agomelatine and gabapentin is a potent anti-allodynic combination in neuropathic rats with the ligated infraorbital or sciatic nerve, which is medicated by α2- and β2-adrenoreceptor noradrenergic neurotransmission [ 23 ]. Considering neuropathic pain is a crucial component of CLBP, agomelatine might possibly alleviate CLBP symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Aydın et al revealed the curative effect of agomelatine on painful diabetic neuropathy in rats and suggested that these effects are mediated by rising synaptic catecholamine levels and through interactions with both α- and β-adrenoceptors [ 22 ]. The study of M’Dahoma et al revealed that co-administration of agomelatine and gabapentin is a potent anti-allodynic combination in neuropathic rats with the ligated infraorbital or sciatic nerve, which is medicated by α2- and β2-adrenoreceptor noradrenergic neurotransmission [ 23 ]. Considering neuropathic pain is a crucial component of CLBP, agomelatine might possibly alleviate CLBP symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…90 Interestingly, agomelatine, a melatonin analog, administration alone had no effect on mechanical allodynia induced by chronic constriction (ligation) injury to the sciatic nerve (CCI-SN) or the infraorbital nerve (CCI-ION) rats but produced an anti-allodynic effect when combined with gabapentin. 91 However, in another study, agomelatine dosedependently decreased mechanical hypersensitivity in three neuropathic pain models (oxaliplatin, streptozocin, and CCI). 92 The analgesic effect of agomelatine remains controversial and needs to be validated.…”
Section: Neuropathic Painmentioning
confidence: 96%
“…60 In addition, agomelatine exhibits anti-allodynia through noradrenergic neurotransmission mediated by α 2 -adrenoceptors and β 2 -adrenoceptors. 91…”
Section: Adrenergic Receptorsmentioning
confidence: 99%
“…Hypothesised superiority of a PGB-MLT combination is based on RCT data indicating that combinations of two mechanistically different treatments show superior efficacy vs either single agent 10-14 43 50-52 and also based on relevant evidence suggesting favourable antinociceptive interactions between these drugs. [53][54][55] Review of sleep outcomes, from RCTs of PGB for pain treatment, has revealed a positive benefit on disturbed sleep through a direct effect on sleep maintenance (ie, staying asleep). Exogenous administration of the pineal hormone, MLT, has been reported to reduce pain in both preclinical and clinical settings (including four fibromyalgia trials), in addition to other RCT evidence of efficacy for primary insomnia and delayed sleep phase syndrome (ie, falling asleep).…”
Section: Pgb-mlt Combinationmentioning
confidence: 99%